2003
DOI: 10.1038/sj.onc.1206232
|View full text |Cite
|
Sign up to set email alerts
|

RRM1-induced metastasis suppression through PTEN-regulated pathways

Abstract: Lung cancer is the leading cause of cancer-related mortality in the United States. Only 15% of patients with this disease survive 5 years or longer. Early metastatic spread is the single most important reason for this poor outcome. The survival of patients with pathological stage I disease, that is, no evidence for metastatic spread, and molecular aberrations on chromosome 11p15.5 is equal to that of patients with stage II disease, that is, metastatic spread to hilar lymph nodes. RRM1 is a gene in this region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 44 publications
6
106
0
3
Order By: Relevance
“…43 A recent study have shown that PTEN reduced phosphorylation of focal adhesion kinase, suppressed invasion and metastasis formation, and increased survival in an animal model. 44 Our preliminary study has indicated that PTEN could be upregulated by AST in HCT 116 cells (Supporting Information Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…43 A recent study have shown that PTEN reduced phosphorylation of focal adhesion kinase, suppressed invasion and metastasis formation, and increased survival in an animal model. 44 Our preliminary study has indicated that PTEN could be upregulated by AST in HCT 116 cells (Supporting Information Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…By immunoblot analysis, PTEN expression was decreased in all malignant cell lines compared with normal hepatocytes ( Figure 7B). Moreover, there was an increase in constitutive tyrosine phosphorylation of FAK, an established downstream target of PTEN 17,18 FAK is a protein tyrosine kinase involved in the regulation of cell-cycle progression, cell survival, and cell migration. Expression of PTEN leads to dephosphorylation of FAK and inhibition of cell migration.…”
Section: Mir-21 Modulates Both Pten Expression and Fak Phosphorylationmentioning
confidence: 99%
“…Clinical and cell biological studies suggest that LOH is an important tumor‐suppressor gene region in lung cancer 15, 16. Moreover, RRM1 is a metastasis suppressor gene through PTEN‐regulated pathways in lung cancer 17. Furthermore, it encodes the regulatory subunit of ribonucleotide reductase which was inhibited by gemcitabine metabolites (5′ diphosphate) 18.…”
Section: Discussionmentioning
confidence: 99%